92 Quality improvement: discharge driving advice for cardiology inpatients. (6th June 2022) - Jones, Oliver; Kapoor, Neel; Hanif, Alina; Kay, Jamie; Ko, Ho Juen; Koslover, Joshua; Sehmi, Joban
Abstract : Background: Many cardiac conditions, including electrophysiologic, ischaemic, or heart failure, are characterised by a risk of sudden and disabling symptoms. For this reason, inpatient cardiology admissions can affect a patient's eligibility to drive, according to driver and vehicle licensing agency (DVLA) rules. Appropriate advice has serious patient quality of life, patient and public safety, and medicolegal implications. Despite this, our own experience, and existing data, suggested that provision of advice was often informal, inaccurate, or omitted altogether. Methods: We conducted a baseline audit of 28 consecutive days of discharge letters against four process measures to establish the frequency and quality of documentation of discharge driving advice for patients discharged from our cardiac care unit. Subsequently, we implemented a quality improvement project (QIP) with prospective patient-centred primary outcome measures. Over six plan-do-study-act (PDSA) cycles, we iteratively designed a standard operating procedure (SOP) for consultant-led discharge driving advice, supported by patient and staff posters, whiteboard magnets and nursing checklists, and a smartphone 'app'. Following the QIP, we audited a second period of 28 consecutive days of discharge letters against the same four process measures to assess lasting change. Results: Baseline audit established that, of 115 consecutive patients, 74 had a diagnosis that could affect their driving eligibility. Of these, one (1.4%) had appropriate documentation of discharge driving advice. Qualitative data collected prospectively throughout the QIP showed positive patient experience and accurate patient understanding as new operating procedures were implemented. Repeat audit of 124 consecutive patients following intervention identified 81 patients who had a diagnosis that could affect their driving eligibility, of whom 36 (44.4%) had appropriate documentation of discharge driving advice. Conclusion: Discharge driving advice is relevant to most cardiology inpatient admissions, and yet was rarely documented. A simple SOP for consultant-led discharge driving advice was developed using PDSA methodology, which was well-received by patients and, following re-audit, demonstrated a lasting improvement in documented advice. Conflict of Interest: None to declare.